Atlas of ceramic fabrics 1 : Italy : North-East, Adriatic, Ionian, Bronze Age, impasto - Cannavò, Valentina (Archaeopress Publishing Ltd, 2018)
This volume presents and interprets the petrographic composition of Bronze Age impasto pottery (23rd-10th centuries BCE) found in the eastern part of Italy. This is the first of a series of Atlases organised according to geographical areas, chronology and types of wares